Adolescents' dietary patterns, their drivers and association with double burden of malnutrition in adolescents: a cross-sectional study in Kenya's urban slums - Milkah N Wanjohi; Elizabeth Wambui Kimani-Murage; Gershim Asiki; Michelle Holdsworth; Rebecca Pradeilles; Nelson Langat; Dickson A. Amugsi; Calistus Wilunda; Kerstin Klipstein-Grobusch (BMC, 2024)
Abstract Background The double burden of malnutrition (DBM) during adolescence is associated with growth and developmental impairment and risk of non-communicable diseases. There is limited evidence on adolescent's dietary patterns (DPs), and how they contribute to DBM in urban low income contexts in sub Saharan Africa. This study assessed DPs of adolescents, their drivers and association with DBM in Kenya's urban slums. Methods Anthropometric, socio-demographic and dietary-intake data were collected through a cross-sectional survey of 621 adolescents from three major urban slums in Nairobi, Kenya. DPs were derived using principal component analysis. Multinomial-logistic-regression was used to assess the association between the DPs, individual and environmental factors and DBM. Results Two DPs were identified: traditional DP (whole grains/cereals, rice, fruits, legumes/nuts, and water) and transitioning DP (refined cereals (maize/wheat), vegetables, meat, tea/coffee, sweet ultra-processed/deep fried snacks). Adolescents from Mathare (the largest slum) were more likely to adhere to the traditional DP (RRR = 3.43; 95% CI 1.85-6.37). Cultural background (Luo) had a positive association (RRR = 4.28; 95% CI 1.97-9.32), while longer residency in the slum (> 10 years) had a negative association (RRR = 0.47; 95% CI 0.25-0.90) with transitioning DP. The transitioning DP had a positive (non-linear) association with overweight/obesity in girls (RRR = 2.79; 95% CI 1.16-6.71). The DPs were not associated with thinness or stunting. Conclusion The DPs indicate various stages of nutrition transition of adolescent diets, which are influenced by cultural background, neighbourhood and duration of stay in the slum. Transitioning DP may expose adolescents to the risks of overweight/obesity in the long-term.